When will this cruel war be over? : the Civil War diary of Emma Simpson - Denenberg, Barry (Dear America, 1996)
The diary of a fictional fourteen-year-old girl living in Virginia, in which she describes the hardships endured by her family and friends during one year of the Civil War.